A COL11A1-correlated pan-cancer gene signature of activated fibroblasts for the prioritization of therapeutic targets. Issue 2 (28th November 2016) - Jia, Dongyu; Liu, Zhenqiu; Deng, Nan; Tan, Tuan Zea; Huang, Ruby Yun-Ju; Taylor-Harding, Barbie; Cheon, Dong-Joo; Lawrenson, Kate; Wiedemeyer, Wolf R.; Walts, Ann E.; Karlan, Beth Y.; Orsulic, Sandra
Highlights: COL11A1 is a highly specific biomarker of activated CAFs in multiple epithelial cancer types. COL11A1 is not expressed in mesenchymal precursors and fibroblasts associated with inflammation and organ fibrosis. Activated CAFs across genetically different epithelial cancer types express a highly conserved gene signature. Abstract: Although cancer-associated fibroblasts (CAFs) are viewed as a promising therapeutic target, the design of rational therapy has been hampered by two key obstacles. First, attempts to ablate CAFs have resulted in significant toxicity because currently used biomarkers cannot effectively distinguish activated CAFs from non-cancer associated fibroblasts and mesenchymal progenitor cells. Second, it is unclear whether CAFs in different organs have different molecular and functional properties that necessitate organ-specific therapeutic designs. Our analyses uncovered COL11A1 as a highly specific biomarker of activated CAFs. Using COL11A1 as a 'seed', we identified co-expressed genes in 13 types of primary carcinoma in The Cancer Genome Atlas. We demonstrated that a molecular signature of activated CAFs is conserved in epithelial cancers regardless of organ site and transforming events within cancer cells, suggesting that targeting fibroblast activation should be effective in multiple cancers. We prioritized several potential pan-cancer therapeutic targets that are likely to have high specificity for activated CAFs and minimal toxicity in normal tissues.